Heterochromatin and gene expression in Drosophila. - Weiler, K.S.; Wakimoto, B.T. (Annual Review of Genetics, 1995)
Heterochromatin is both necessary for the expression of heterochromatic genes and inhibitory for the expression of euchromatic genes. These two properties of heterochromatin have been elucidated from the study of chromosome rearrangements that induce position effect variegation (PEV) in Drosophila melanogaster. Novel euchromatin-heterochromatin junctions can affect the expression of euchromatic and heterochromatic genes located several megabases away, distinguishing higher order chromatin structure from most other regulatory mechanisms. Studies of PEV promise insights into the basis for heterochromatin formation and the role of higher order chromatin and chromosome structure in gene regulation. We evaluate the models and experimental data that address the mechanisms of PEV in different cell types, the potential functions of modifiers of PEV, and the relationship of PEV to other phenomena associated with variegated gene expression in Drosophila.